Biomarker‐Calibrated Protein Intake and Physical Function in the Women's Health Initiative. Issue 11 (28th October 2013) - Beasley, Jeannette M.; Wertheim, Betsy C.; LaCroix, Andrea Z.; Prentice, Ross L.; Neuhouser, Marian L.; Tinker, Lesley F.; Kritchevsky, Stephen; Shikany, James M.; Eaton, Charles; Chen, Zhao; Thomson, Cynthia A.
<x xml:space="preserve">Abstract</x> Objectives To determine whether preservation of physical function with aging may be partially met through modification in dietary protein intake. Design Prospective cohort study. Setting Women's Health Initiative (WHI) Clinical Trials (CT) and Observational Study (OS) conducted at 40 clinical centers. Participants Women aged 50 to 79 (N = 134, 961) with dietary data and one or more physical function measures. Measurements Physical function was assessed using the short‐form RAND‐36 at baseline and annually beginning in 2005 for all WHI participants and at closeout for CT participants (average ~7 years after baseline). In a subset of 5, 346 participants, physical performance measures (grip strength, number of chair stands in 15 seconds, and timed 6‐m walk) were assessed at baseline and Years 1, 3, and 6. Calibrated energy and protein intake were derived from regression equations using baseline food frequency questionnaire data collected on the entire cohort and doubly labeled water and 24‐hour urinary nitrogen collected from a representative sample as reference measures. Associations between calibrated protein intake and each of the physical function measures were assessed using generalized estimating equations. Results Calibrated protein intake ranged from 6.6% to 22.3% energy. Higher calibrated protein intake at baseline was associated with higher self‐reported physical function (quintile (Q)5, 85.6, 95% confidence interval (CI) = 81.9–87.5; Q1, 75.4, 95% CI = 73.2–78.5, Ptrend = .002) and a slower rate of functional decline (annualized change: Q5, −0.47, 95% CI = −0.63 to −0.39; Q1, −0.98, 95% CI = −1.18 to −0.75, Ptrend = .02). Women with higher calibrated protein intake also had greater grip strength at baseline (Q5, 24.7 kg, 95% CI = 24.3–25.2 kg; Q1, 24.1 kg, 95% CI = 23.6–24.5 kg, Ptrend = .04) and slower declines in grip strength (annualized change: Q5, −0.45 kg, 95% CI = −0.39 to −0.63 kg; Q1, −0.59 kg, 95% CI = −0.50 to −0.66 kg, Ptrend = .03). Women with higher calibrated protein intake also completed more chair stands at baseline (Q5, 7.11, 95% CI = 6.91–7.26; Q1, 6.61, 95% CI = 6.46–6.76, Ptrend = .002). Conclusion Higher calibrated protein intake is associated with better physical function and performance and slower rates of decline in postmenopausal women.